Emociones en el aprendizaje, de estudiantes de 8vo año paralelo A y B del Colegio de Bachillerato “27 de Febrero” periodo 2023-2024 - Riofrio Labanda, Gabriela Katherine (2024)
The objective of this curricular integration work was to identify students' emotions and how it affects their learning, taken as a sample from the "27 de Febrero" High School for the period 2023-2024, with 8th year students, parallels A and B. Understanding and managing their emotions allowed them to develop key skills for academic and personal success, such as the ability to concentrate. For this study, a qualitative approach was used along with descriptive, inductive, analytical, synthetic and scientific methods. The instruments applied included the interview directed to the teachers and the observation guide to the students. According to the results obtained, it was determined that the presence of positive and negative emotions among the students occurred more when knowing the academic performance of each one; Another of its important results was the motivation of the students, observing that the extrinsic motivation occurred mostly with the teacher's intervention to help the students understand and grasp what was explained. As a last objective, an educational proposal was developed, which could be of great help in the students' learning process. This study highlighted the importance of emotions in students and how a professional could detect their impact in time, allowing for appropriate intervention.